Quantum State Transfer and Network Engineering - Nikolopoulos, Georgios M.; Jex, Igor.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Faithful communication is a necessary precondition for large-scale quantum information processing and networking, irrespective of the physical platform. Thus, the problems of quantum-state transfer and quantum-network engineering have attracted enormous interest over the last years, and constitute one of the most active areas of research in quantum information processing. The present volume introduces the reader to fundamental concepts and various aspects of this exciting research area, including links to other related areas and problems. The implementation of state-transfer schemes and the engineering of quantum networks are discussed in the framework of various quantum optical and condensed matter systems, emphasizing the interdisciplinary character of the research area. Each chapter is a review of theoretical or experimental achievements on a particular topic, written by leading scientists in the field. The volume aims at both newcomers as well as experienced researchers.
Spin Chains as Data Buses, Logic Buses and Entanglers -- Communication in Engineered Quantum Networks -- Dual- and Multi-rail Encoding -- Quantum State Transfer with Limited Resources -- Robustness of Spin-chain State-transfer Schemes -- Implementation of State Transfer Hamiltonians in Spin Chains with Magnetic Resonance Techniques -- State Transfer Hamiltonians in Photonic Lattices.
Keywords: Physics; Software engineering; Quantum theory; Telecommunication; Physics; Quantum Information Technology, Spintronics; Communications Engineering, Networks; Quantum Physics; Special Purpose and Application-Based Systems; Quantum Computing